Cooling of mechanical vibrations by heat flow - Kulinich, S.I.; Gorelik, L.Y. (Физика низких температур, 2018)
We theoretically consider a nanomechanical link between two metallic leads subject to a temperature drop. It is shown that mechanical dynamics of such system can be strongly affected by a heat flow through it via the position dependent electron-electron interaction, even though the electronic transport between leads is blocked. In particular, it is demonstrated that, under certain conditions, the stationary distribution of the excitations in the mechanical subsystem has a Boltzmann form with an effective temperature, which is much lower than the temperature of the environment; this seems rather counterintuitive. We also find that a change in the direction of the temperature gradient can result in the generation of mechanical vibrations rather than the heating of the mechanical subsystem. We theoretically consider a nanomechanical link between two metallic leads subject to a temperature drop. It is shown that mechanical dynamics of such system can be strongly affected by a heat flow through it via the position dependent electron-electron interaction, even though the electronic transport between leads is blocked. In particular, it is demonstrated that, under certain conditions, the stationary distribution of the excitations in the mechanical subsystem has a Boltzmann form with an effective temperature, which is much lower than the temperature of the environment; this seems rather counterintuitive. We also find that a change in the direction of the temperature gradient can result in the generation of mechanical vibrations rather than the heating of the mechanical subsystem. Рассмотрена наномеханическая связь между двумя металлическими электродами, которые поддерживаются при различной температуре. Показано, что механическая динамика в такой системе существенным образом определяется тепловым потоком. Существование ненулевого теплового потока обусловлено электрон-электронным взаимодействием, при этом поток заряда между электродами отсутствует. Установлено, что при определенных условиях стационарное распределение возбуждений в механической подсистеме имеет вид больцмановской функции распределения с эффективной температурой, которая значительно ниже температуры электродов. Также показано, что изменение направления градиента температуры приводит к механическим колебаниям, а не к нагреву механической подсистемы.